Molecular characterization and optimization of parameters for cultivation of Pleurotus himalayaensis - ABHISHEK KATOCH*, PREM NATH SHARMA; SUBHASH DHANCHOLIA, NAIYA SHARMA, POOJA KAPOOR (Indian Phytopathology, 2016)
A new species of Pleurotus proposed as Pleurotus himalayaensis Dhancholia grows in association with a threatened plant of Ferula jaeschkeana Vatke at an altitude of 4000mts and above in the Himalayas was collected from Lahaul valley. People in Lahoul valley found the mushroom to be highly delicious. Isolates were collected from ten different locations in the valley. In preliminary attempts it was found that mycelial run was fast on PDA and malt extract media among different growth media tested whereas temperature at 28Â°C with pH of 6 was found to be most congenial for vegetative growth. Cultivation technology for fruiting of this Pleurotus species was developed with locally available substrate i.e. Albizia chinenesis sawdust + cotton seed cake supplemented with 10 per cent wheat bran at 500-800 lux and it was found to be best in terms of primordial initiation, number of primordia, fruit body expansion and development. Though the new species had different morphological characteristics but genetic sequence analysis based on internal transcribed spacer marker revealed it as closely related to P. eryngii.